Drought and stand susceptibility to attacks by the European spruce bark beetle: A remote sensing approach. (5th September 2022) - Nardi, Davide; Jactel, Hervé; Pagot, Elodie; Samalens, Jean‐Charles; Marini, Lorenzo
Abstract: Several time‐series analyses have demonstrated that after extreme summer drought bark beetle damage increased. However, studies predicting stand susceptibility over large spatial extents are limited by technical constraints in obtaining detailed, spatially‐explicit data on infestation spot occurrence. Using a unique dataset of georeferenced bark beetle infestation data, we tested whether the spatial variation of local growing conditions of forest stands, topography, and landscape variables modified the local occurrence of Ips typographus infestations after a severe hot drought in Central Europe. Bark beetle infestation occurrence depended on soil‐related aridity intensity, elevation, slope, and soil conditions. We showed that elevation interacted with growing conditions and topography. At low elevations, spruce forests growing on flat areas and wetter soils were more sensitive to the infestations. On the contrary, forests on steep slopes and soils with low water availability were rarely attacked. At the landscape scale, bark beetle damage increased with host tree cover but decreased with compositional diversity. Our findings are generally consistent with the growth‐differentiation balance hypothesis that predicts that trees growing under chronic dry conditions tend to be more resistant against biotic disturbances. Spruce stands at low elevations located in homogeneous landscapes dominated by spruce were those more exposed to bark beetles in the initial phase of a drought‐induced outbreak.